The Adaptation of Cloud Solution for Peer Collaboration Work among Teachers in Maktab Nasional Secondary School - Romella Marie Sipaul (OUM, 2021)
In Maktab -in and analysed in Microsoft Excel spreadsheets stored in one local computer. Teachers need to wait in turns to input marks. It is time consuming and hinders productivity at work. This study aims to examines the capabilities of google drive solution and to evaluate its implementation effectiveness in peer-to-peer collaboration among teachers to manage students' assessment records. The two research questions for this study were: (1) How does google drive solution able to manage student assessment records at Maktab Nasional? and (2) How to evaluate the effectiveness of google drive implementation in managing student assessment record at Maktab Nasional? A set of task-based assessment and a survey questionnaire were formulated for data collection, consisting of a demographic item, a five-point Likert-scale with 26 items followed by listing 3 negative and 3 positive aspects of google drive and lastly, 4 open-ended items about teache all perception. The sample population of 6 teachers were surveyed using purposive sampling technique. The data for this study was collected during the school break on mid-June 2021. The survey results were analysed using basic descriptive statistics as well as coded thematic analysis to help answer the research questions. The results from the research instruments indicated that the cloud solution is an effective form of peer collaboration among teachers. In addition, participants expressed that the process of managing student assessment records have improved significantly from the google drive implementation.